Interior Design’s Social Contribution to Intentional Communal Living Arrangements: Perceptions of Residents - Torry, Caitlan-Rose (The IIE, 2022)
The intended research study ‘Interior Design’s Social Contribution to Intentional Communal Living Arrangements: Perceptions of Residents’ is an exploratory study that aims to understand the benefits that living in an Intentional Communal Living Arrangement can have on the single residents living in them. The study explores how these spaces designed for social interaction can have a positive impact on single residents’ social well-being, mental health, and physical health. Through the use of in-depth interviews, the researcher gains a deep understanding of how single residents living in Intentional Communal Living Arrangements use the spaces designed for social interaction, how they feel about these certain spaces, and how they feel that these spaces have had an impact on both their physical and mental health. The results of this study have the potential to increase our understanding of the impact that social interaction and the spaces designed for social interaction has on single residents living in Intentional Communal Living Arrangements.
Keywords: Communes; Mental health; Well-being; Social interaction; Health